The effect of semicarbazide on the nature and stability of collagen fibrils - Ayad, Shirley (1970)
Semicarbazide affected both the final width and stability of fibrils reconstituted from solutions of acid-soluble collagen. Fibril width was increased after semicarbazide treatment at pH2.6 and 4.3, whereas after treatment at pH8.9 it decreased. Fibril stability was decreased after semicarbazide treatment at all values of pH and temperature, indicating the inhibition of intermolecular cross-linking. A direct binding of semicarbazide to the αβ-unsaturated aldehyde groups in the intramolecular cross-link was demonstrated.